IDENTIFYING THE FUNCTIONING ENVIRONMENT AND ANALYZING THE ACTIVITIES OF DOMESTIC ENTERPRISES: STRATEGIC DIMENSIONS (Development Service Industry Management, 2023)
The article takes a look at the current state of business environment of Ukraine. The attention is on the study of peculiarities of functioning of complex socio-economic systems, including industrial companies. The dynamics of gross domestic product, nominal and real GDP from 2017 to 2022 in particular, was given. By doing this, the major tendencies and trends in the development of the economy in the new conditions of the high intensification of conflicts not only in the domestic but also in the world market were outlined, which directly affects the domestic industry and its institutional support.  The changes of gross domestic product in Ukraine with reflection of nominal GDP per capita is given. The structure of final use of Ukraine's GDP during 2017-2022 is examined. It is shown that a significant part of Ukraine's GDP is aimed at consumption (the consumer spending ranges from 85,6 to 104,2% in it’s structure). So, the consumer demand is growing. The analysis shows a decrease in gross accumulation as a percentage of GDP which explained by economic slowdown in Ukraine, volatile situation that arose from the hostilities leads to a reduction in investment in the production expansion or modernization, attracting less internal and external investments. It is proved that in all spheres of socio-economic development of Ukraine in 2022, negative trends were prevalent. The energy crisis with interrupted operational processes during air alerts affected real wages. The article reports a significant decrease in the index of industrial production for different types of activity and main industrial groups in 2022. The trend indicates both the loss of the country's industrial potential and the problems in domestic consumer demand due to economic difficulties caused by the war. The decline in the index of light industry products is a sign that effective strategies need to be developed and implemented to improve  economic conditions and recovery of industrial growth. We believe that economic security should be given special attention since Ukraine is currently in a state of full-scale war.
Keywords: analyzing; diagnosing; environment; strategy; enterprise; dynamics; crises